Humidity sensor using surface adsorbed channel modulated GrapheneNanoribbon : NEGF approach - Shakil, Shifur Rahman; Fatema Tuz Zohra; Pramanik, Parna; Tushar, Raihanul Islam (BRAC University, 2014)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2014.